REMOTE SENSING IN ARCHAEOLOGY: AN OVERVIEW - Rosa Lasaponara; Nicola Masini (Havacılık ve Uzay Teknolojileri Dergisi, 2013)
Recently, the importance of applying satellite remote sensing technology to archaeological research has been paid great attention worldwide, due to the following aspects: